Hannah's night - Sakai, Komako, 1966- (Gecko Press, 2013)
When everyone is asleep, Hannah wakes up and discovers the quiet, exciting night-time world. When Hannah wakes suddenly in the night, she discovers a whole new world of adventure. With nobody awake to tell her off, she can do just as she pleases. The book combines simple language with beautifully textured images, capturing the innocence and wonder of young children at play.